2018
DOI: 10.3897/natureconservation.25.23776
|View full text |Cite
|
Sign up to set email alerts
|

Infanticide in brown bear: a case-study in the Italian Alps – Genetic identification of perpetrator and implications in small populations

Abstract: Sexually Selected Infanticide (SSI) is thought of as a male reproductive strategy in social mammalian species, because females who lose cubs may quickly re-enter oestrus. SSI has rarely been documented in non-social mammals and, in brown bears, SSI has been studied mainly in an eco-ethological perspective. The authors examined the first genetically documented infanticide case which occurred in May 2015 in brown bears in Italy (Trentino, Central-Eastern Alps). The infanticide killed two cubs and their mother. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In fact, we estimated relatively low genetic diversity in the studied Italian bear populations, especially with regard to Uam , with three loci being monomorphic. The Uam population was characterized by an even lower genetic diversity compared to Uaa (uHe = 0.368 vs. 0.627; GD = 0.40 vs. 0.61), confirming the results reported in [ 33 , 34 ]. Since the management of both these small populations depends on regular genetic analyses, the BEST set of identified markers will be critical to keeping the cost-benefit ratio in favor of continued monitoring.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In fact, we estimated relatively low genetic diversity in the studied Italian bear populations, especially with regard to Uam , with three loci being monomorphic. The Uam population was characterized by an even lower genetic diversity compared to Uaa (uHe = 0.368 vs. 0.627; GD = 0.40 vs. 0.61), confirming the results reported in [ 33 , 34 ]. Since the management of both these small populations depends on regular genetic analyses, the BEST set of identified markers will be critical to keeping the cost-benefit ratio in favor of continued monitoring.…”
Section: Discussionsupporting
confidence: 88%
“…Polymorphism and genotyping errors of the CURRENT panel were extrapolated from [ 33 ] ( Uam ) and [ 34 ] ( Uaa ) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We did come across some lack of clarity that would be helpful to address in future research. There were many reports of infanticide, and although some authors assumed that cannibalism always accompanies infanticide (e.g., Davoli et al 2018), most studies neglected to report whether or not the cubs were consumed after being killed. For the sake of our literature review of cannibalism, we only considered the cases where a conspecific was reported to be consumed, but this means that our literature review may have underestimated cannibalism events by bears, especially cases of sexually selected infanticide, which is the most common form of cannibalism.…”
Section: Discussionmentioning
confidence: 99%